Promotion and integrated marketing communications - Semenik, Richard J.
No other book better prepares studentsfor the innovations in Microsoft Office 2007 like the second edition of DIGITOOLS! Part of Thomson South-Western's BUSINESS OF TECHNOLOGY series, DIGITOOLS also teaches the proper way to key and format documents using proven instructional methods, while also emphasizing computer applications, such as word processing, presentations, spreadsheets, and database. Students learn to effectively use the Internet and input technologies, including speech and handwriting recognition